From Nostalgia to locus amoenus: Polish Migrants’ Memoirs in Canada and the Idea of Home, Identity, and Belonging - Dagmara Drewniak (European Journal of American Studies)
The aim of this article is to analyze the latest volume of migrant memoirs from Poland to Canada Zwyczajna przeprowadzka / An Ordinary Move: Memoirs of Polish Immigrants in Canada 1988-2012 (2014) in order to track the changes in attitudes to the migrants’ perception of Poland and Canada in the context of finding/losing home, (un)belonging and Polish-Canadian identity. This edited collection and its examination will be situated within the history of Polish life writing in Canada as well. The texts gathered in the volume are written in prose and verse and prove the migrants’ variegated perspectives ranging from nostalgic and painful tones discussed in light of Svetlana Boym’s The Future of Nostalgia to affirmative ones that can be described through the concept of finding a friendly space or the so called locus amoenus (Shallcross). This contribution also addresses the question of the usage of Polish and English as languages of expression as the recent publication is the first bilingual edition in the series. All in all, the memoirs show not only the constant need to write one’s experience of migration and narrate the immigrants’ attitude to their Polish identity but also testify to the possibility of migrants’ “transnational status” (Kozaczka 152).